Three-compartment body composition changes in professional rugby union players over one competitive season: A team and individualised approach - Lees, M. J.; Oldroyd, B.; Jones, B.; Brightmore, A.; Barlow, M. J.; Hind, K. (Journal of Clinical Densitometry, 2016)
Identifying and understanding changes in the body composition of rugby players during the competitive season is important from both performance and health perspectives. We investigated three-compartment body composition across one competitive season in professional male rugby union players using dual-energy X-ray absorptiometry (DXA). Thirty-five players from one English Premiership team (forwards: n=20, age: 25.5±4.7 years; backs: n=15, age: 26.1±4.5 years) received a total-body DXA scan at preseason (August), midseason (January) and endseason (May), enabling quantification of body mass, total and regional fat mass, lean mass, percentage tissue fat mass (%TFM) and bone mineral content (BMC).